Dietary Patterns and Their Relationship With Semen Quality. Issue 3 (May 2018) - Jurewicz, Joanna; Radwan, Michał; Sobala, Wojciech; Radwan, Paweł; Bochenek, Michał; Hanke, Wojciech
Diet is a complex exposure variable, which calls for multiple approaches to examine the relationship between diet and disease risk. To address these issues, several authors have recently proposed studying overall dietary patterns by considering how foods and nutrients are consumed in combinations. The aim of the study was to investigate the associations between dietary patterns, semen quality parameters, and the level of reproductive hormones. The study population consisted of 336 men who attended the infertility clinic for diagnostic purposes and who had normal semen concentration of 20 to 300 mln/ml or slight oligozoospermia (semen concentration of 15-20 mln/ml). Participants were interviewed, and a semen sample was provided by them. Diet was assessed via food frequency questionnaire, and dietary patterns were identified by factor analysis. Men were classified into three groups according to scores of each dietary pattern: Western, Mixed, or Prudent. A positive association was observed between sperm concentration and Prudent dietary pattern, and level of testosterone and Prudent dietary pattern ( p = .05, p = .03, respectively). Additionally, Prudent dietary pattern was identified to decrease the DNA fragmentation index ( p = .05). The results were adjusted for sexual abstinence, age, smoking, past diseases, and alcohol consumption. Higher consumption of a Prudent dietary pattern was associated with higher sperm concentration and higher level of testosterone. Sperm chromatin structure was inversely related to higher consumption of a Prudent dietary pattern. Further research is needed to confirm these findings and extend these results to other populations.